(untitled) (Journal of Asian Development Studies, 2025)
The present study aimed to explore the relationship of social media addiction with social Anxiety. This study was derived from pilot testing of M.Phil. research work. A correlational design was employed in this cross-sectional survey of college and university students in Balochistan. A total of 149 participants were recruited from four universities and four colleges in Balochistan to complete standardised measures of the Social Media Addiction Scale – Student Form (SMA-SF; Sahin, 2018) and the Social Anxiety Questionnaire for Adults (SAQ-30; Caballo, 2013). Age of the participants ranged between 15 and 30 years. Through Pearson correlation analysis, a strong positive and statistically significant relationship was observed between social media addiction and social Anxiety. Results indicated social media addiction as a positive and important predictor of social Anxiety as the predictor variable explained a 20% variance in the outcome variable. A higher level of social media addiction was reported in male participants, and in terms of institutional differences, university students experienced greater social media addiction than college students. No significant mean difference was observed based on gender or institution of Social Anxiety. The results of the present study align with the findings reported in past research and support the assumptions of Social Cognitive Theory, which suggests that online actions can create and maintain feelings of Anxiety. The results indicate that addressing digital behaviours should be a priority in mental health programs targeting young people.